Technology convergence capability and firm innovation in the manufacturing sector: an approach based on patent network analysis. (15th November 2018) - Kim, Keungoui; Jung, Sungdo; Hwang, Junseok
Abstract : As a consequence of the convergence between manufacturing technology and the foundation technologies of Industry 4.0, it is becoming more important for firms to formulate an innovation strategy for their technological capabilities. In this context, the present study measures firm‐level technology convergence (TC) capability using patent network analysis. A firm's TC capabilities are measured using three centrality indices pertaining to a patent network, which is constructed based on the relationship between patents and their international patent classification. For the empirical analysis, panel regression is conducted to observe the effect of TC capabilities on innovation for the top 30 firms in four manufacturing industries. We find that the TC degree positively influences the firms' overall innovation, namely their total number of patents, and negatively influences their convergent innovation, calculated as the ratio between the number of TC patents and the total number of patents, while the effect of TC betweenness is the opposite. These findings imply that while concentrating on similar technologies may promote quick technology application, it could hamper the enhancement of a TC's potential. To promote TC, a firm should thus develop technologies more likely to be involved in TC.